Literature as Fetishism: some Consequences for a Theory of Translation - Arrojo, Rosemary (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThis article looks at different attempts to define literary and poetic texts and the claim of untranslatability with regard to these. It studies the relationship between author, reader and text and concludes that every act of translation, and reading, implies the innate unpredictability of human relationships constantly driven by the desire to transform all things we create into some form of autobiography.